Perbandingan Modifikasi Bentuk Lambung Terhadap Tahanan Kapal Menggunakan Metode "Delftship" - Indro Dwi Cahyo (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
This study aims to analyze the resistance on vessels that have a single hull shape of the hard-chine type is modified to a multi-chine types using the "DELFTShip" method. This research includes research on the development of the "DELFTShip" method using a speedboat sample of the Vocational School - Undip, where the ship plans to be modified on the hull that was originally hard-chine to multi-chine, with a qualitative approach using the "DELFShip version 4.03.68" method which can later be known differences in the value of ship resistance (RT).Results showed that the resistance value (RT) at a speed of 3 knots there is a difference -0.0332 kN, at a speed of 4 knots there is a difference of 0.0925 kN, and at a speed of 5 knots there is a difference 0.3205. By referring to the number of Froude Number. , stomach with multi-chine type has the value of prisoner (RT) is better than the stomach with hard-chine type.